1949
DOI: 10.1111/j.1151-2916.1949.tb18942.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHATE GLASS: PbO‐WO3‐P2O5 SYSTEM*

Abstract: The glass-formation region has been determined for the PbO-W03-P205 system$ and certain physical properties of representative glasses have been measured. Glasses of the system show an unusually high X-ray and gamma-ray absorption and are not readily discolored when exposed to X rays. Equations have been developed from which specific volumes and lead equivalents may be calculated from composition. Because of their high index of refraction and relatively low dispersion these glasses are also useful for optical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1957
1957
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…3 correspond to the data of the typical oxide and fluoride glasses [39], respectively. The oxide glasses include quartz glass [40], borosilicate glass (Iwaki Glass Co. COVER 18-18), PbO-WO 3 -P 2 O 5 -CdO-TiO 2 glass [41] and various oxide glasses in the literature found in the INTER-GLAD database [39] in this case. ZBLAN [24,25,[35][36][37][38] glass etc.…”
Section: Resultsmentioning
confidence: 99%
“…3 correspond to the data of the typical oxide and fluoride glasses [39], respectively. The oxide glasses include quartz glass [40], borosilicate glass (Iwaki Glass Co. COVER 18-18), PbO-WO 3 -P 2 O 5 -CdO-TiO 2 glass [41] and various oxide glasses in the literature found in the INTER-GLAD database [39] in this case. ZBLAN [24,25,[35][36][37][38] glass etc.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, amorphous WO 3 thin films were intensively investigated because of their significant advantages over other materials on reversibility, stability and color efficiency [2,3]. In the case of tungsten-based glasses, it was shown that the introduction of WO 3 can improve considerably the chemical durability and thermal stability against devitrification [4][5][6][7]. In addition, these glasses can exhibit particular optical properties such as upconversion phenomena when doped with Tm 3+ or two-photon nonlinear absorption for the most WO 3 concentrated samples [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This work intents to define a new group of fluorophosphate glasses, tungstate fluorophosphate glasses based on the ternary NaPO 3 -BaF 2 -WO 3 association. It was expected that tungsten oxide content would influence significantly thermal and optical properties [8][9][10]. Especially, large WO 3 concentrated vitreous samples would be very stable against devitrification [11][12][13][14][15] and would present special properties observed in crystalline WO 3 such as thermochromism, photochromism [16,17] or non-linear optical properties [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%